Antiulcer effects of Zataria multiflora Boiss. on indomethacin-induced gastric ulcer in rats - Mohsen Minaiyan; Sayed-Ebrahim Sajjadi; Kamran Amini-Dehkordi (Mashhad University of Medical Sciences, 2018)
Objective: Zataria multiflora has been reported to have several medicinal properties including antioxidant, antibacterial, antispasmodic, and expectorant activities. This study aimed to investigate the effect of Z. multiflora hydro-alcoholic extract (ZMHE) on peptic ulcer caused by indomethacin in rats. Materials and Methods: ZMHE was prepared by maceration,  condensed by rotary evaporator and dried by a freeze-drier. In this study, 72 male Wistar rats were randomly divided into 12 groups, six in each including: normal rats, control rats, ranitidine-treated, and animals that were treated with ZMHE (100, 200, 400 mg/kg). Parenteral and oral treatments were done 1 and 2 hours, respectively before gastric ulcer induction by indomethacin (25 mg/kg, i.p.). After 6 hours, animals were sacrificed, two sides of the stomach were ligated and gastric contents and tissues were investigated in terms of pH and biochemical and histologic parameters, respectively. Results: ZMHE (at all doses) considerably decreased the ulcer area and ulcer severity in comparison to control group after oral and parenteral administration. Oral administration of this extract increased thepH of stomach contents while diminished pepsin activity in a dose-dependent manner. Following parenteral treatment, a significant difference in pH of stomach content was observed only by ZMHE 400mg/kg in comparison to control group. The myeloperoxidase (MPO) enzyme activity decreased in groups that received the extract via both oral and parenteral routes. Conclusion: It might be concluded that ZMHE could protect against experimental gastric ulcer induced by indomethacin and this action is probably mediated via reducing acid secretion and pepsin activity besides enhancing tissue antioxidant capacity